Sexually dimorphic role of the locus coeruleus PAC1 receptors in regulating acute stress-associated energy metabolism - Duesman, Samuel J.; Shetty, Sanutha; Patel, Sanil; Ogale, Neha; Mohamed, Farzanna; Sparman, Njeri; Rajbhandari, Prashant; Rajbhandari, Abha Karki (Frontiers in Behavioral Neuroscience, 2022)
Severe stress leads to alterations in energy metabolism with sexually dimorphic onset or severity. The locus coeruleus (LC) in the brainstem that mediates fight-or-flight-or-freeze response to stress is sexually dimorphic in morphology, plays a key role in interactions between diet and severe stressors, and has neuronal input to the brown adipose tissue (BAT)- a thermogenic organ important for energy balance. Yet, little is known on how LC coordinates stress-related metabolic adaptations. LC expresses receptors for the neuropeptide PACAP (pituitary adenylate cyclase activating peptide) and PACAP signaling through PAC1 (PACAP receptor) are critical regulators of various types of stressors and energy metabolism. We hypothesized that LC-PAC1 axis is a sex-specific central “gatekeeper” of severe acute stress-driven behavior and energy metabolism. Selective ablation of PAC1 receptors from the LC did not alter stress response in mice of either sex, but enhanced food intake in females and was associated with increased energy expenditure and BAT thermogenesis in male mice. These results show a sexually dimorphic role of the LC-PAC1 in regulating acute stress-related energy metabolism. Thus, by disrupting LC-PAC1 signaling, our studies show a unique and previously unexplored role of LC in adaptive energy metabolism in a sex-dependent manner.